NILAI TAMBAH JAMUR TIRAM CRISPY “DuCrija Mush Chi” (STUDI KASUS IKM ANHAN MEKARSARI DI DESA NGARUM KECAMATAN NGRAMPAL KABUPATEN SRAGEN) - Handayani, Siska Tri; Dewati, Rosita; Setyarini, Agung (Journal of Agribusiness, Social and Economic, 2022)
Crispy oyster mushrooms are snacks made from oyster mushrooms and produced by IKM Anhan Mekarsari, Ngarum Village, Ngrampal District, Sragen Regency. The purpose of this study was to determine the costs, revenues, efficiency and added value of the Crispy Oyster Mushroom “DuCrija Mush Chi”. The research method used is descriptive. IKM Anhan Mekarsari was choosen because it already has a P-IRT permit and halal certificate. Respondents in this study were the owner and 2 production employees. Analysis methods were used cost, revenue, income, efficiency and value added analysis. The results of this study are the total cost for produce crispy oyster mushroom is about Rp. 12.506.059 includes fixed costs (Rp. 176,648) and variable cost (Rp. 12.329.411). Revenue in a month is Rp.25.500.000. The income aerned is Rp. 12.993.941. The revenue and cost ratio of IKM Anhan Mekarsari is 2,5 which means if the R/C Ratio >1 then the business is feasible, the B/C Ratio 1,45 which means >1 the business is profitable. The added value obtained from processing oyster mushrooms in one production cycle is Rp. 115.385/Kg. The added value ratio shows 60,7%, it can be categorized as high added value for IKM Anhan Mekarsari because it more than 40% and the profit obtained from processing oyster mushrooms become crispy oyster mushrooms is Rp. 61.974?Kg of raw materials or about 88% of the product value per unit raw materials.   Keywords: Hayami, Oyster, Mushroom, Value Added.